NOD/SCID IL2Rγ-null mouse xenograft model of human p53-mutated chronic lymphocytic leukemia and ATM-mutated mantle cell lymphoma using permanent cell lines. Issue 11 (2nd November 2015) - Verner, Jan; Trbusek, Martin; Chovancova, Jana; Jaskova, Zuzana; Moulis, Mojmir; Folber, Frantisek; Halouzka, Roman; Mayer, Jiri; Pospisilova, Sarka; Doubek, Michael
Abstract : Xenograft models represent a promising tool to study the pathogenesis of hematological malignancies. To establish a reliable and appropriate in vivo model of aggressive human B-cell leukemia and lymphoma we xenotransplanted four p53-mutated cell lines and one ATM-mutated cell line into immunodeficient NOD/SCID IL2Rγ-null mice. The cell lines MEC-1, SU-DHL-4, JEKO-1, REC-1, and GRANTA-519 were transplanted intraperitoneally or subcutaneously and the engraftment was investigated using immunohistochemistry and flow cytometry. We found significant differences in engraftment efficiency. MEC-1, JEKO-1 and GRANTA-519 cell lines engrafted most efficiently, while SU-DHL-4 cells did not engraft at all. MEC-1 and GRANTA-519 massively infiltrated organs and the whole intraperitoneal cavity showing very aggressive growth. In addition, GRANTA-519 cells massively migrated to the bone marrow regardless of the transplantation route. The MEC-1 and GRANTA-519 cells can be especially recommended for in vivo study of p53-mutated chronic lymphocytic leukemia and ATM-mutated mantle cell lymphoma, respectively.